Proceedings of the 2nd Information Technology and Mechatronics Engineering Conference (ITOEC 2016TOEC 2016) 2016
DOI: 10.2991/itoec-16.2016.57
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Factors of Online Shopping Intention for Fresh Agricultural Products Based on UTAUT2

Abstract: Abstract. To analyze the factors influencing online shopping intention for fresh agricultural products, this paper constructs a research model based on UTAUT2. Data obtained from questionnaires are processed using structural equation model. The results show that performance expectancy, effort expectancy, hedonic motivation, facilitating conditions have positive impacts on the online shopping intention for fresh agricultural products, gender has a significant influence on the measuring model, while neither expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 7 publications
(5 reference statements)
4
25
1
1
Order By: Relevance
“…Furthermore, it was identified that behavior intention towards m-payment of Cambodian users is affected significantly by performance expectancy and the same result was found in the studies of Ghalandari (2012), Ayoade (2015), and Ali Sair and Danish (2018). The effect of effort expectancy on behavior intention towards m-payment was significant and this result was supported by An et al (2016), Catherine et al (2017), Fadzil (2018. In addition, SEM analysis showed that EE1 to EE5 was affected significantly by effort expectancy as latent variable in which EE4 received highest effect.…”
Section: Discussion Of Empirical Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, it was identified that behavior intention towards m-payment of Cambodian users is affected significantly by performance expectancy and the same result was found in the studies of Ghalandari (2012), Ayoade (2015), and Ali Sair and Danish (2018). The effect of effort expectancy on behavior intention towards m-payment was significant and this result was supported by An et al (2016), Catherine et al (2017), Fadzil (2018. In addition, SEM analysis showed that EE1 to EE5 was affected significantly by effort expectancy as latent variable in which EE4 received highest effect.…”
Section: Discussion Of Empirical Resultsmentioning
confidence: 53%
“…The effect of effort expectancy on behavior intention is found as significant in previous empirical evidences. An et al (2016) found significant effect of effort expectancy on online shopping intention among 387 users. Catherine et al (2017) studied behavior intention towards fingerprint authentication-based ATMs in Uganda and they confirmed that behavior intention was received significant and positive effect from effort expectancy.…”
Section: Research Model and Hypothesismentioning
confidence: 88%
“…The unified theory of acceptance and use of technology (UTAUT) model was an attempt to unify and strengthen theories about technology acceptance (Ajzen & Fishbein, 1988; Davis et al, 1989; Rogers, 2003; Venkatesh & Davis, 2000). The model has been applied and tested with a diverse range of technologies, including online shopping (An, Han, & Tong, 2016), mobile banking services (Gharaibeh, Arshad, & Gharaibeh, 2018), mapping apps (Gupta & Dogra, 2017), NFC mobile payments in hotels (Morosan & DeFranco, 2016), social recommender systems (Oechslein, Fleischmann, & Hess, 2014), desktop‐based computer software (Sharma & Kumar, 2012) and health and fitness apps (Yuan, Ma, Kanthawala, & Peng, 2015). Venkatesh, Morris, Davis, and Davis (2003) incorporated three additional constructs, namely hedonic motivation (HM), PV and habit, extending UTAUT into UTAUT2, also known as the extended unified theory of acceptance and use of technology.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Escobar-Rodríguez and Carvajal-Trujillo [17] had applied UTAUT2 in e-commerce websites to purchase online tickets. Morosan and DeFranco [18] applied UTAUT2 in hotel mobile payments, whereas [19] explored UTAUT2 in online shopping for fresh agricultural products.…”
Section: Review Of Relevant Theoretical Modelsmentioning
confidence: 99%
“…Performance expectancy is the extent to which an individual believes that the use of technology will bring numerous advantages in performing activities [14]. Most of the researchers [18,19,[31][32][33] had concluded that performance expectancy has a direct positive relationship towards behavioural intention in using apps, as performance expectancy reflects the perceived usefulness and advantages that benefit the users to adopt mobile apps. Based on the above, the first hypothesis is developed: H1: There is a positive relationship between performance expectancy and behavioural intention to use mobile apps…”
Section: Performance Expectancymentioning
confidence: 99%